Zirconium(IV) and Hafnium(IV)-Catalyzed Highly Enantioselective Epoxidation of Homoallylic and Bishomoallylic Alcohols - Li, Zhi (2010)
[Image: see text] In this report, zirconium(IV) and hafnium(IV)-bishydroxamic acid complexes were utilized in the highly enantioselective epoxidation of homoallylic alcohols and bishomoallylic alcohols, which used to be quite difficult substrates for other types of asymmetric epoxidation reactions. The performance of the catalyst was improved by adding polar additive and molecular sieves. For homoallylic alcohols, the reaction could provide epoxy alcohols in up to 81% yield and up to 98% ee, while for bishomoallylic alcohols, up to 75% yield and 99% ee of epoxy alcohols rather than cyclize compounds could be obtained in most cases.